A robust infinite-horizon optimal control approach to climate economics - Babonneau, Frédéric; Haurie, Alain; Vielle, Marc (Central European journal of operations research, 2025)
An infinite-horizon optimal control paradigm is proposed to model the global energy transition to zero-net emissions when carbon dioxide removal (CDR) and electric fuel (E-Fuel) technologies become available. Infinite-horizon optimal trajectories for convex systems are often characterized by global asymptotic stability, where an attractor exists, which is defined as an extremal steady state. In our approach, this asymptotic attractor, known as the ‘turnpike’, represents a sustainable future with zero net emissions. The turnpike can be obtained by solving an “implicit” mathematical programming problem where we introduce robustness for taking into account some important uncertainties on the availability of $$\hbox {CO}_2$$ CO 2  storage. The complete mathematical description of an infinite-horizon optimal control formulation is complemented by the numerical illustration which shows results that are consistent with the goals of Paris-agreement.